Impact Study on Rajasri Birds as Backyard Poultry in Nandyal District of Andhra Pradesh - Goud, E. Ravi; Krishnamurthy, A.; Adinarayana, M.; Dhanalakshmi, G.; Prasad, J. V. (International Journal of Bio-resource and Stress Management, 2026)
A Study was conducted during the month of June, 2023 to March, 2024 to examine the socio-economic status, nutritional security, employment generation, and adoption constraints among marginal and landless farmers who reared Rajasri birds in backyard poultry in Nandikotkur, Jupadu Bunglow, and Kothapalli mandals of Nandyal district, Andhra Pradesh. Using a purposive and stratified random sample of 60 farmers across six villages, data were collected through structured interviews and analyzed using descriptive statistics, paired t-tests with Cohen’s d effect size, and Rank Based Quotient (RBQ) for constraint ranking. Results showed that of 30 chicks purchased, mortality stood at 16.66%, 36.66% were sold, 16.66% consumed, and 30% retained. Egg production generated both income (77.97% of 168 eggs sold monthly) and home nutrition (15.47% consumed). Significant improvements were observed post adoption: meat consumption frequency (d=2.38), egg consumption frequency (d=3.94), and annual egg intake nearly doubled (d=12.33); annual income rose by ` Rs. 16,634 (d=0.70). Employment generated 36.54 mandays annually, and was largely contributed by women and children. Major constraints included lack of broodiness, predator threats, low market acceptance, not consider as desi bird, high feed cost, and management difficulties. The study concluded that Rajasri’s backyard poultry substantially enhanced household wellbeing but required targeted support to overcome adoption barriers,and promote sustainable livlihood opportunities for small and marginal farming communities in the region.